INFOGRAPHICS AS A MEANS OF COMMUNICATING AND DISSEMINATING TECHNOLOGIES IN SMALL-SCALE DAIRY FARMS FROM CENTRAL MEXICO - Gabriela Martínez-Álvarez; Carlos Manuel Arriaga-Jordán; Isabel Blanco-Penedo; Carlos Galdino Martínez-García (Tropical and Subtropical Agroecosystems)
Background. The information and communication technologies are considered important for the rapid and efficient communication and dissemination of information among farmers, which can facilitate the diffusion of technologies. Objective. To identify the most relevant technologies to dairy farmers and to analyse farmers’ perception of the information contained in the infographics shared via WhatsApp™. Methodology. To collect the data, a questionnaire was applied to 108 dairy farmers from central Mexico. Farmers were grouped using multivariate statistics such as factor and cluster analysis. The four most important technologies to farmers were identified and infographics of maize silage, artificial insemination (AI), concentrate feeding, and heat-service were designed and distributed via WhatsApp™™. A Chi-Square test was conducted to analysed the dichotomous responses about farmers’ perception of receiving and sending infographics via WhatsApp™. The infographics were also evaluated using a five-point Likert type scale and Kruskal-Wallis test was used to analyse the data. Results. Four factors that explain 73.3% of the cumulative variance were identified. Four groups were identified. Group 1 had the largest farm size, group 2 had the most available family labour, group 3 had the youngest farmers with better schooling, and group 4 had the highest level of technical assistance. Farmers in groups 1 and 2 found the infographics on maize silage and AI to be informative and well-understood. Farmers in group 3 found the concentrate feeding infographic to be informative, but 73% reported that pH and ruminal acidity were terms difficult to understand. Meanwhile, 87% of farmers in group 4 found the heat-service infographic to be unimportant, but easy to comprehend. Implications. The research contributed to identifying the usefulness of infographics in communicating information on technologies important to farmers. It also identified areas of interest achieved through their use in extension services.  Conclusions. It is concluded that the infographics and WhatsApp™ are very useful tools for sharing information and communication of technologies. Therefore, the combination of these tools could improve extension services for dairy farmers in rural areas.